2021
DOI: 10.3390/su13084139
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Climatic Conditions, Season and Environmental Factors on CO2 Concentrations in Naturally Ventilated Primary Schools in Chile

Abstract: Between the ages of 6 and 18, children spend between 30 and 42 h a week at school, mostly indoors, where indoor environmental quality is usually deficient and does not favor learning. The difficulty of delivering indoor air quality (IAQ) in learning facilities is related to high occupancy rates and low interaction levels with windows. In non-industrialized countries, as in the cases presented, most classrooms have no mechanical ventilation, due to energy poverty and lack of normative requirements. This fact he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Extensive research conducted in developing countries has consistently demonstrated the significant health implications of poor IAQ [30]. A compelling body of research underscores the critical need for strategic actions and improvements to safeguard the health and well-being of students in these environments [31][32][33][34][35].…”
Section: Iaq In Schools (Oecd Countries)mentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive research conducted in developing countries has consistently demonstrated the significant health implications of poor IAQ [30]. A compelling body of research underscores the critical need for strategic actions and improvements to safeguard the health and well-being of students in these environments [31][32][33][34][35].…”
Section: Iaq In Schools (Oecd Countries)mentioning
confidence: 99%
“…Pollutants generated from the outside environment result from outdoor activities, weather conditions, location, and the proximity of school classrooms to roads [40]. Another factor that seriously impacts the IAQ includes window operating actions, as in naturally ventilated classrooms, it plays a vital role compared to mechanically ventilated classrooms [32].…”
Section: Iaq In Schools (Oecd Countries)mentioning
confidence: 99%
“…Maintaining good IAQ in the classroom is not a simple and easy task. As observed in many studies, classrooms did not meet the IAQ requirement of relevant standards over 50% of the time [12,14,25]. This is often caused by a lack of adequate ventilation, particularly in winter, because occupants usually have less willingness to Indoor Air open windows and doors in cold weather to ensure thermal comfort needs.…”
Section: Thermal Comfort Of Studentsmentioning
confidence: 99%
“…Maintaining good IAQ in schools is challenging. Díaz et al [12] conducted a study in 8 primary schools in Chile. They found that the indoor CO 2 concentration exceeded the maximum threshold for around 70% of school hours in winter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation